MENINGKATKAN PROFESIONALISME GURU DALAM MENGHADAPI TANTANGAN GLOBAL DI ERA REVOLUSI INDUSTRI 4.0 - Susi Susanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The era of industrial revolution 4.0 as an era marked by various challenges where these challenges can be beneficial and foster good luck if understood its characteristics. But it can also be a dangerous threat if it is wrong in responding. Teachers are expected to always learn so that they can face the challenges that exist, due to advancing and guiding students in a good direction, which is expected by this nation, namely as the next generation of creative, innovative and so on.